Adverse childhood experiences and depression among women in rural Pakistan - Katherine LeMasters; Lisa M. Bates; Esther O. Chung; John A. Gallis; Ashley Hagaman; Elissa Scherer; Siham Sikander; Brooke S. Staley; Lauren C. Zalla; Paul N. Zivich; Joanna Maselko (BMC, 2021)
Abstract Background Adverse Childhood Experiences (ACEs) are a common pathway to adult depression. This pathway is particularly important during the perinatal period when women are at an elevated risk for depression. However, this relationship has not been explored in South Asia. This study estimates the association between ACEs and women's (N = 889) depression at 36 months postpartum in rural Pakistan. Method Data come from the Bachpan Cohort study. To capture ACEs, an adapted version of the ACE-International Questionnaire was used. Women's depression was measured using both major depressive episodes (MDE) and depressive symptom severity. To assess the relationship between ACEs and depression, log-Poisson models were used for MDE and linear regression models for symptom severity. Results The majority (58%) of women experienced at least one ACE domain, most commonly home violence (38.3%), followed by neglect (20.1%). Women experiencing four or more ACEs had the most pronounced elevation of symptom severity (β = 3.90; 95% CL = 2.13, 5.67) and MDE (PR = 2.43; 95% CL = 1.37, 4.32). Symptom severity (β = 2.88; 95% CL = 1.46, 4.31), and MDE (PR = 2.01; 95% CL = 1.27, 3.18) were greater for those experiencing community violence or family distress (β = 2.04; 95%; CL = 0.83, 3.25) (PR = 1.77; 95% CL = 1.12, 2.79). Conclusions Findings suggest that ACEs are substantively distinct and have unique relationships to depression. They signal a need to address women's ACEs as part of perinatal mental health interventions and highlight women's lifelong experiences as important factors to understanding current mental health. Trial registration NCT02111915 . Registered 11 April 2014. NCT02658994 . Registered 22 January 2016. Both trials were prospectively registered.